Dupont Advisory Committee on Agricultural Innovation & Productivity For The 21St Century - NA (2011)
The world is faced with the vast challenge of meeting ever-increasing food demands placed on the agriculture sector due to a rapidly growing population. In fact, the world population has been increasing by an estimated 78 million each year, about the size of the population of Germany.1 Challenges around food security – ensuring there is enough food to meet demand – will be exacerbated when the population surpasses 9 billion by 2050 and 10 billion by the turn of the century.2 Global food production must be 70 percent greater than today’s level to close the deficit between supply and demand, commonly referred to as the productivity gap.3 And, it must be done without using substantially more land. With current grain stocks at historically low levels and food demand increasing at rates higher than production, the challenge is not decades into the future, but is here today.